Filtering Media by Electrospinning Next Generation Membranes for Separation Applications (Springer International Publishing, 2018)
This book covers the state-of-the-art on electrospun materials for the use of filters for water remediation, ion-exchange membranes and affinity membranes for the capture of selected chemical and biochemical species, as well as filtering applications covering air treatment, defense and protective applications, and oil-water separation. The book also provides an overview of the landscape of marketed electrospun filters and of technical approaches for the large scale production of nanofibrous non-woven filter media. This is an ideal book for biomaterials and polymer researchers interested in the applications of filtering media by electrospinning. Covers the latest research on ion-exchange membranes and affinity membranes for capture of cells and biological substances Broadens reader understanding of antimicrobial electrospun filters and sieving filters for liquid microfiltration Reviews exhaustively the key recent research into electrospun filters for oil-water separation, heavy metals removal, and defense and protective applications.